LANGUAGES AND THE SELF - Komorowska, Hanna (Neofilolog, 2019)
The article looks into the meaning of concepts of L2 Self, L2 Ideal self and L2 Motivational Self Systems from the point of view of their usefulness for SLA/FLT research. Psychological and sociological terminology related to the Self, Identity, Storied Self, Social Identity and Ethnicity is then discussed as well as various types of the Self useful in the analysis of attitudes to first, second and foreign languages. Examples of linguistic decisions are offered that lead to language maintenance, language loss or changes of the dominant language. Linguistic behaviour is traced back to possible ways of presenting the Self as well as to different approaches to ethnicity, integration and assimilation. Conclusions and implications for classroom language learning and teacher education are also presented.